The Determinants of Capital Structure: An Empirical Study of SMEs in Developing Countries of East Asia and Pacific Region - Lee, Hui Jinn (2016)
The study explores the determinants of capital structure in 9,026 SME firms in fourteen developing countries of East Asia and Pacific Region for the period years of 2006 – 2014. The secondary data from the World Bank Business Environment and Enterprise Performance Survey (BEEPS) and the World Development Indicator (WDI 2014) have been collected for the study. The study has selected eight independent variables which include firm level variables and macroeconomic level variables as determinants and two dependent variables. The dependent variables are namely bank financing of short-term investment and bank financing of long-term investment while the independent variables that have been used in this study are firm size, firm age, profitability, financing access difficulties, audited financial statement, inflation rate, lending interest rate and GDP growth rate. The factors affecting the dependent variables have been studied. In conclusion, the firm size, firm age, inflation rate, audited financial statement and financing access difficulties have a positive impact on bank financing of short-term investment, whereas in long-term perspective, variables such as firm age, audited financial statement and financing access difficulties have a positive impact on bank financing of long-term investment. Finally, this study found that all variables are contributing factors in determine the dependent variable of bank financing of short-term investment while firm size, firm age, profitability and GDP growth rate are the only contributing factors in determine the dependent variable of bank financing of long-term investment.